Formulation and Evaluation of Herbal Cream from Ivy Gourd and Other Natural Excipients - Bheeman, Saranya; Karuppusamy, Nithyapriya; Balakrishnan, Sangameswaran; Ponnusamy, Sutha; Ravi, Saranya; senthilkumar, Yuvashree (Journal of Neonatal Surgery, 2025)
The acceptance and appeal of cosmetic formulations based on herbs have significantly increased in recent years. Products that are seen as natural, secure, and eco-friendly are becoming more and more popular. Herbal cosmetics are preferred not only because they have few adverse effects but also because they are biocompatible with the skin and can provide therapeutic benefits by using bioactive chemicals obtained from plants. Coccinia grandis, also referred to as Ivy gourd, is one of the many medicinal plants being investigated for cosmeceutical uses. A member of the Cucurbitaceae family, this climbing vine has long been utilized in herbal medicine systems to treat infections, inflammation, and skin conditions. Its antibacterial, antioxidant, and anti-inflammatory qualities are attributed to the abundance of phytochemicals found in its leaves, including flavonoids, alkaloids, tannins, and saponins. The development and assessment of a topical herbal cream with Ivy gourd extract as the main active ingredient is the main goal of this study. To improve the cream's moisturizing, restorative, and protecting qualities, additional natural excipients have been added to the recipe in addition to Ivy gourd, including aloe vera gel, beeswax, shea butter, and coconut oil. Careful plant material extraction, emulsion preparation, and natural base mixing are all steps in the formulation process. Numerous physicochemical and microbiological evaluation factors, including pH, spreadability, viscosity, stability, and antibacterial activity, are also described in this article. The encouraging outcomes of these evaluations demonstrate the potential of Ivy gourd as a key botanical ingredient in the creation of herbal skincare products that are sustainable, safe, and efficacious